Access and Equity in Family Law and Civil Status Issue for the General Courts of Indonesia - Tim PPIM UIN Jakarta (Studia Islamika, 2009)
The subject area of the access and equity study in the General Courts will focus on family issues (divorce, child guardianship) and civil status issues (e.g. provision of letters to the Civil Registry authorizing the issuing of birth certificates in certain cases). The research may include the area of inheritance by disregarding the criminal issues filed at the courts.DOI: 10.15408/sdi.v16i2.487